Interventions to prevent hypothermia in extremely preterm low-weight infants undergoing cardiac catheterisation. Issue 3 (19th September 2022) - Alhalabi, Eliane; Zestos, Maria; Kobayashi, Daisuke; Mckelvey, George M; Taylor, Rachel A
Abstract : Background: In January 2019, a new device called the Amplatzer Piccolo Occluder was approved by the US Food and Drug Administration for percutaneous closure of patent ductus arteriosus in infants weighing more than 700 g and of postnatal age more than 3 days. Premature low-weight infants are predisposed to hypothermia when transported outside of the thermo-neutral environment. At our institution, 90% of extremely preterm low-weight infants developed transient moderate hypothermia in the cardiac catheterisation suite. Methods: We conducted a study testing multiple hypotheses aimed at preventing hypothermia in the cardiac catheterisation suite. Interventions included increasing ambient room temperature, reducing exposure to cold environment and reducing overall time spent in the remote location. The primary outcome was the proportion of patients who developed transient hypothermia at the start of the procedure in the cardiac catheterisation suite. The secondary measures included mean core body temperature at four different instances, as well as anaesthesia time, procedure time and radiation exposure. Results: During the study period, 10 patients were enrolled in each group. The postintervention group saw a reduction in transient hypothermia from 90% to 40% (absolute risk reduction 50%, p=0.02). Data analysis showed an improvement in mean core body temperature (35.4°C vs 36.4°C, p<0.01) as well as a smaller percentage drop in temperature (4% vs 1.3%, p<0.01) between the two groups, both of which were statistically significant. The anaesthesia time, procedure time and radiation exposure reduced between the two groups. Conclusion: The application of the interventions reduced hypothermia in this high-risk population. The implementation of a protocol with collaboration of a multidisciplinary team is indispensable in providing optimal care to extremely preterm infants.